How Do Online News Genres Take Up Knowledge Claims From a Scientific Research Article on Climate Change?. (January 2019) - Bray, Nancy
The Internet has helped to change who writes about science in the news, how news is written, and how it is taken up by different audiences. However, few studies have examined how these changes have impacted the uptake of scientific claims in online news writing. This case study explores how online news genres take up knowledge claims from a research article on climate change over a period of one year and shows how shifting boundaries between rhetorical communities affect genre uptake. The study results show that online news writers predominantly use the news report genre to cover research findings for 48 hours, after which they predominantly use the news editorial genre to engage these findings. Analysis suggests that the news report genre uses the press release and the article abstract as intermediary genres, but the news editorial uses only the abstract. I argue that the switch between genres repositions the scientist, the journalist, and the public epistemologically, a reorientation that favors uptake in news media outlets supporting action to mitigate climate change and its effects.